The definitive VAT system and its impact on tax collection - Hana Zídková; Kristýna Balíková (European Journal of Government and Economics (EJGE), 2021)
Value Added Tax (VAT) is a significant source of fiscal revenues in the EU. However, the VAT treatment of cross-border supplies enables large-scale tax frauds, such as the Missing Trader Intra-Community (MTIC), which takes each year billions of euros from Member States' public budgets. In 2016 a definitive VAT system was proposed by the European Commission to respond to the shortcomings of the current temporary system. This new system should reduce the possibilities of MTIC fraud for intra-community transactions through the collection of VAT by the supplier in the same way as for domestic transactions. The tax collection by the supplier would impact the administrative costs of the financial authorities. This paper contributes to the discussion about the advantages and disadvantages of the newly suggested system. The analysis focuses on the study of the change in administrative costs and VAT revenues for individual Member States and across the EU. The results are that after implementing the definitive VAT system, total administrative costs of the Member States would increase at least by EUR 107 million, whereas total VAT revenues would rise by EUR 40 billion. This indicates the overall positive impact of the definitive VAT system for the EU. However, individual Member States would not benefit equally. The net exporters, whose intra-community supplies exceed the intra-community acquisitions, would spend more than others for the collection of VAT in connection with the international trade of goods.
Keywords: H21; H26; K34; 330; definitive VAT system; international trade statistics; VAT action plan; temporary VAT system; MTIC fraud